2019
DOI: 10.3329/bjo.v24i2.44154
|View full text |Cite
|
Sign up to set email alerts
|

Study of Pathological Variations of Solitary Thyroid Nodule

Abstract: Objective: To find out the incidence of malignancy in patient with solitary thyroid nodule. Methods: This cross-sectional study was carried out with 100 solitary thyroid nodular patients who admitted in Otolaryngology & Head-Neck Surgery Department of Sir Salimullah Medical College Mitford Hospital (SSMCMH) & Bangabondhu Sheikh Mujib Medical Univercity (BSMMU), Dhaka, from July 2012 to December 2013, where all patients were admitted throughout patient department. All patients were selected as per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Papillary carcinoma was more common than follicular carcinoma. This finding is supported by the work of Al Mamun et al 12 Lin et al has reported that 23.3% of nodule were malignant and papillary carcinoma was more common which partially support our study. 13 Khadilkar UN et al has reported that non neoplastic lesions like involuting nodules were common which support our study.…”
Section: Discussionsupporting
confidence: 92%
“…Papillary carcinoma was more common than follicular carcinoma. This finding is supported by the work of Al Mamun et al 12 Lin et al has reported that 23.3% of nodule were malignant and papillary carcinoma was more common which partially support our study. 13 Khadilkar UN et al has reported that non neoplastic lesions like involuting nodules were common which support our study.…”
Section: Discussionsupporting
confidence: 92%
“…We had a low incidence of cancer in our study and therefore, very low incidence of dysphagia, hoarseness of voice and stridor. 5,6 Lymphadenopathy correlated with the presence of malignancy with 8 of the 13 patients showing an FNAC proof of malignancy. We can conclude that presence of lymphadenopathy in the presence of a thyroid swelling has high possibility of a sinister presence, usually Papillary carcinoma and every effort should be made by the clinician both clinically and US scan wise to discover lymphadenopathy.…”
Section: Discussionmentioning
confidence: 95%
“…10 They are 3-4 times more frequent in women than men. 11 An increase in prevalence rate in women was observed particularly in age group 21-30 years which might be associated with infertility, pregnancy and other complications. 12 Most of the thyroid nodules are benign and fewer than 5% of them are actually malignant.…”
Section: Introductionmentioning
confidence: 99%